Hadiths And Their Ways Of Usage In The Education Of Pupils - 1Shodiev Fakhriddin Teshevich; 2Saydulloyeva Shoxsanam Mashrafjonovna (Researchparks Publishing, 2022)
The article provides a brief overview of the hadiths and ideas on how to use them in educating students. It has been analyzed with evidence that the hadiths are the brightest light on the path to the perfection of the readers.